SOCIAL ASPECT OF SUPPORT OF SMALL BUSINESS AND PROBLEMS OF MIGRATION IN GERMANY - V. A. Onuchak (Vestnik MGIMO-Universiteta, 2016)
The flow of refugees in Germany is a political migration at which the flow of migrants increases load of the budget due to payments of social benefits. At first sight, apparently, the existing privileges and incentives of creation of small and medium-sized enterprises (MSP) rather big and that problems inemployment of such number of migrants shouldn't be. They will take potential workplaces or will open the business, but a question in, whether it is possible to occupy the arrived migrants in small business in the territory of Germany. However, unlike labor migration which increases self-employment of the population, political migration of such effect can't give. At present it is necessary to limit global migration of the same Germany if the country intend store the economy. Positive influence of a migratory stream on national economy will be short-term, connected with increase in demand. In the near future refugees will demand considerable expenses of the budget as they don't pay taxes or pay them in a smaller size, demand additional expenses on safety in the social sphere.